2006
DOI: 10.1111/j.1540-8167.2006.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Quality of Life in Patients with Transient Loss of Consciousness

Abstract: TLOC seriously affects QoL, especially in patients with a recent onset of clinical symptoms and those suffering from both syncopal and presyncopal episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 23 publications
4
87
0
6
Order By: Relevance
“…suggested that healthy teenagers and young adult subjects using the beat-to-beat measurement of stroke volume with calculation of CO and systemic vascular resistance (SVR) have established that CO actually increases with the onset of standing up, whereas SVR falls markedly. [31][32][33][34] This study confirms the findings suggested by Tschakovsky et al and Rossberg and Penaz that the fall in BP after arising from squatting is based primarily on a fall in SVR. [35,36] In accordance with the previous studies in healthy young adults, the CO at the moment of the nadir was increased, however, for the large initial fall in BP on standing after supine rest, the hemodynamic mechanism can be either a large fall in CO or in SVR.…”
Section: Discussionsupporting
confidence: 81%
“…suggested that healthy teenagers and young adult subjects using the beat-to-beat measurement of stroke volume with calculation of CO and systemic vascular resistance (SVR) have established that CO actually increases with the onset of standing up, whereas SVR falls markedly. [31][32][33][34] This study confirms the findings suggested by Tschakovsky et al and Rossberg and Penaz that the fall in BP after arising from squatting is based primarily on a fall in SVR. [35,36] In accordance with the previous studies in healthy young adults, the CO at the moment of the nadir was increased, however, for the large initial fall in BP on standing after supine rest, the hemodynamic mechanism can be either a large fall in CO or in SVR.…”
Section: Discussionsupporting
confidence: 81%
“…Esta situação clínica que condiciona um marcado impacto na qualidade de vida dos doentes, estando associada a uma elevada morbilidade, risco de lesões físicas e absentismo laboral 2,3 . A síncope reflexa (SNc) é a sua forma mais comum, apresentando uma maior incidência em adultos jovens 4,5 .…”
Section: Introductionunclassified
“…Disease-specific measures assess the impact on daily living and facilitate comparisons between studies in patients with the same disease (e.g. SFSQ and ISQL) [14,27,39]. Efforts should focus on understanding the mechanisms of psychological and social impairment through qualitative research.…”
Section: Direction For Clinical Services and Researchmentioning
confidence: 99%
“…Generic instruments permit comparisons across populations and economic analysis (e.g. SF-36) [14,39]. Disease-specific measures assess the impact on daily living and facilitate comparisons between studies in patients with the same disease (e.g.…”
Section: Direction For Clinical Services and Researchmentioning
confidence: 99%